Preparation method of ceramic powder with core-shell structure, preparation method of green ceramic tape and application

By forming polymer cladding on the surface of the ceramic powder, the problems of uneven mixing and particle breakage in the flexible raw ceramic belt are solved, the high dispersion and bonding strength of the ceramic powder are achieved, and the performance of the ceramic material after sintering is improved .

CN119306501APending Publication Date: 2025-01-14MAXONE SEMICON CO LTD

Patent Information

Application Number
CN202411487852.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing flexible raw ceramic belts have problems of uneven mixing and particle breakage during the ball milling process, resulting in insufficient dispersion and bonding strength of the ceramic powder, making it difficult to produce high-strength and dense ceramic materials under low temperature conditions.

Method used

Rotary chemical vapor deposition method is used to form polymer polymer encapsulation on the surface of ceramic powder, forming ceramic powder with core-shell structure, and mixing it with additives to prepare higher dispersion and bonding through rotary chemical vapor deposition method. Ceramic powder of strength, used to prepare flexible raw ceramic tapes.

Benefits of technology

Achieve uniform dispersion and high bonding strength of ceramic powder, improve the strength, fracture toughness and density of ceramic materials after sintering, reduce the proportion of adhesive, overcome the defects of ball mill mixing, and improve the quality of raw ceramic belts. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306501A_ABST
    Figure CN119306501A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of ceramic powder with a core-shell structure, and a preparation method and application of a green tape. The preparation method comprises the following steps: mixing basic powder with multiple precursor materials forming the cladding material by adopting a rotary chemical vapor deposition method, reacting the multiple precursor materials at a reaction temperature, and generating a high-molecular polymer cladding outside the basic powder. The problems of uneven mixing, particle crushing caused by long-time mixing and the like in ball-milling mixing can be solved; in addition, the coating effect of the binder can be better, the dispersity of the ceramic powder is better, and the ceramic powder is more controllable and not agglomerated in the subsequent sintering process. The method has the advantages that the precursor reacts on the surface of the basic powder to form a core-shell structure, so that the ceramic powder is single in size, small in size and high in dispersity, and the low-temperature ceramic material manufactured by sintering the material has higher strength, higher fracture toughness and higher density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor manufacturing technology, and in particular to a method for preparing a ceramic powder having a core-shell structure, a method for preparing a green ceramic tape, and applications thereof. Background Art

[0002] Flexible green ceramic tape is the main raw material for producing low-temperature ceramic sheets (LTCC). In related technologies, flexible green ceramic tape is made by mixing solid particles such as glass and ceramic with organic additives, and is manufactured through operations such as tape casting, drying and cutting. At present, the raw slurry of green ceramic tape is mostly ball milled. The control of ball milling mixing time has a very significant impact on the quality of the raw slurry. Short ball milling mixing time causes uneven mixing of powder particles, and too long ball milling mixing time will cause powder particles to break. The slurry viscosity is too high, which makes it impossible to carry out the tape casting process. At the same time, since additives are easy to agglomerate, dispersants must be added, otherwise it is difficult to mix evenly with ceramic powders. Summary of the invention

[0003] The present application provides a method for manufacturing a ceramic powder with a core-shell structure, which can improve the uniformity of the combination of a basic powder and a binder without damaging the morphology of the basic powder, so that the ceramic powder has better dispersibility and bonding strength in subsequent processing.

[0004] In order to achieve the above objectives, this application adopts the following technical solutions: The present application provides a method for preparing a ceramic powder with a core-shell structure, which uses a rotary chemical vapor deposition method to mix a basic powder with a plurality of precursor materials that form a shell material, react the plurality of precursor materials at a reaction temperature, and generate a high molecular polymer shell outside the basic powder.

[0005] The polymer coating is mainly a binder material. Therefore, the above technical solution solves some drawbacks in ball milling mixing, such as uneven mixing and particle breakage caused by long-term mixing. On the other hand, it can make the binder wrapping effect better, the dispersion of ceramic powder better, and more controllable and non-agglomerated in the subsequent sintering process. The advantage of the present invention is that the core-shell structure is formed by the reaction of the precursor on the surface of the basic powder, so that the ceramic powder has a single size, a small volume, and a high dispersibility. The low-temperature ceramic material sintered with this material has higher strength, higher fracture capriciousness, and greater density.

[0006] In a possible implementation, the basic powder is a mixture of one or more materials selected from the group consisting of ceramic, glass, and alumina.

[0007] In a possible implementation, the high molecular polymer shell is polyimide, polyvinyl butyral or polyvinylidene fluoride.

[0008] In a possible implementation, the high molecular polymer shell is polyimide, and the precursor material includes pyromellitic dianhydride and diaminohexane.

[0009] In a possible implementation, before deposition begins, the basic powder is loaded into a reaction tank of a deposition device, and the reaction tank is evacuated; and the plurality of precursors are added into corresponding raw material tanks.

[0010] In a possible implementation, the raw material tank is heated to make the multiple precursors undergo phase change to form gases, the raw material tank is connected to a reaction tank of a deposition device, and the temperature of the reaction tank is maintained to be greater than or equal to the reaction temperature of each of the precursors.

[0011] In a possible implementation, an inert gas is introduced into the raw material tank, so that the inert gas carries the decomposed precursor gas in the raw material tank to the reaction tank.

[0012] In a possible implementation, the flow rate of the inert gas is 20-160 sccm.

[0013] In a possible implementation, during the deposition process, the rotation speed of the reaction tank is set to 30-50 rpm.

[0014] In a possible implementation, the preparation method comprises the following steps: S1. The basic powder is loaded into the reaction tank of the deposition equipment, and the plurality of precursor materials are placed into the corresponding raw material tanks; S2. Evacuate the reaction tank to make the pressure inside the reaction tank less than 100Pa; S3. Heating the reaction tank and the raw material tank, maintaining the temperature of the reaction tank at 300-500°C, and maintaining the temperature of the raw material tank at 150-250°C, so that the precursor undergoes a phase change to form a gas; S4 connects the raw material tank and the reaction tank, introduces an inert gas into the raw material tank, carries the precursor gas to the deposition tank, and the ventilation flow rate of the inert gas is 20-160sccm; S5. During the deposition process, the reaction tank is kept at a rotation speed of 30-50 rpm, so that the basic powder is evenly suspended in the mid-air in the reaction tank, so that the precursor can be evenly contacted with the basic powder, and react and deposit on the surface of the powder; S6. After the reaction is finished, collect the ceramic powder with the polymer coating. Another purpose of the present application is to provide a method for preparing a green ceramic tape, which can overcome the defects of ball milling mixing and obtain a flexible green ceramic tape with uniform mixing and high dispersibility.

[0015] The present application provides a method for preparing a green ceramic tape, comprising the steps of preparing a ceramic powder having a core-shell structure by using the preparation method described in any one of the first aspects above, and mixing and stirring the ceramic powder having a core-shell structure with an additive to form a slurry, and using the slurry to prepare a flexible green ceramic tape.

[0016] Since the basic powder has been fully combined with the binder during the rotary chemical vapor deposition process, a uniformly wrapped ceramic nanopowder can be obtained. The ceramic nanopowder with a core-shell structure has better dispersibility and a single size. The ceramic powder is then mixed with the additive and fully stirred, so the uniformity of the green ceramic tape can be improved. The ceramic material (such as LTCC) after the green ceramic tape is stacked and sintered will have higher strength, higher fracture capriciousness, and higher density. The technical solution reduces the proportion of the binder in the slurry.

[0017] In a possible implementation, the additive does not contain a dispersant.

[0018] In a possible implementation, the mass ratio of the ceramic powder to the additive is 8 to 12:1.

[0019] In a possible implementation, the additive includes a plasticizer; or, the additive includes a solvent and a plasticizer; or, the additive includes a binder, a solvent and a plasticizer; or, the additive includes a solvent, a binder, a plasticizer and a dispersant.

[0020] The present application also provides an application of ceramic powder prepared by rotary chemical vapor deposition in the preparation of green porcelain tape, which uses rotary chemical vapor deposition to form a polymer shell on the surface of a basic powder to form a ceramic powder with a core-shell structure, and uses the ceramic powder with a core-shell structure to prepare green porcelain tape.

[0021] It can be understood that the above-mentioned application may include the ceramic powder prepared by the rotary chemical vapor deposition method provided above. Therefore, the beneficial effects that can be achieved can refer to the beneficial effects provided above and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of the structure of a deposition device provided in an embodiment of the present application.

[0023] Figure 2This is a photo of the green porcelain tape obtained by ball milling under an electron microscope in the related technology.

[0024] Figure 3 This is a photo of the green porcelain tape provided in the examples of the present application under an electron microscope.

[0025] Among them: 1. reaction tank; 2. first raw material tank; 3. second raw material tank; 4. vacuum pump; 5. first valve; 6. second valve. DETAILED DESCRIPTION

[0026] To describe the technical content, structural features, achieved purpose and effect of the invention in detail, the technical scheme in the embodiment of the present application will be described below in conjunction with the drawings in the embodiment of the present application. Obviously, the described embodiment is only a part of the embodiment of the present application, rather than all the embodiments. In the following description, for the purpose of explanation, many specific details are set forth to provide a detailed description of various exemplary embodiments or implementations of the invention. However, various exemplary embodiments may also be implemented without these specific details or in the case of one or more equivalent arrangements. In addition, various exemplary embodiments may be different, but not necessarily exclusive. For example, without departing from the inventive concept, the specific shape, structure and characteristics of the exemplary embodiment may be used or implemented in another exemplary embodiment.

[0027] The present application provides a method for preparing a ceramic powder having a core-shell structure, which is to use a rotary chemical vapor deposition method to mix a basic powder with a plurality of precursor materials for forming a shell material, to react the plurality of precursor materials, and to generate a high molecular polymer shell outside the basic powder. The plurality of herein includes two or more.

[0028] The basic powder can be made of one or more materials selected from ceramic, glass and alumina. The particle size of the basic powder is selected to be 100-150nm.

[0029] The polymer coating acts as a binder in the production process of the green porcelain tape, uniformly wraps the outside of the basic powder, and is mixed with other additives such as plasticizers and dispersants to form a slurry. It is understandable that the material of the polymer coating can be selected from the binder material desired to be used in the preparation process of the green porcelain tape, for example, polyimide (PMM A ), polyvinyl butyral resin (PVB), or polyvinylidene fluoride (PVDF).

[0030] In the first embodiment of the present application, the polymer shell is polyimide. Therefore, in the process of rotary chemical vapor deposition, the added precursor materials include pyromellitic anhydride (PMDA) and diaminohexane (DAH). Under the heating environment, the two phases change to gaseous state and undergo polymerization reaction to form polyamic acid (PAA), which is then formed into polyimide (PMM) through thermal cyclization or chemical imidization process. A ), the product is deposited on the outside of the suspended basic powder to form a shell.

[0031] In other embodiments, when the high molecular polymer shell is made of polyvinyl butyral resin, the precursor material includes diacyl chloride, diol, diamine, etc.

[0032] like Figure 1 As shown, the deposition equipment includes a reaction tank 1, a plurality of raw material tanks and a vacuum pump 4. In this embodiment, the raw material tanks include a first raw material tank 2 and a second raw material tank 3. The first raw material tank 2 and the second raw material tank 3 are connected to the reaction tank 1 through a pipeline. A second valve 6 is also provided on the pipeline. The second valve 6 can be adjusted to open or close the passage between each raw material tank and the reaction tank. In addition, each raw material tank has an air inlet pipeline, which is opened or closed by the first valve 5. When the air inlet pipeline is opened, a carrier gas can be introduced into the raw material tank. Usually, the carrier gas is an inert gas, such as argon Ar. In some implementations, the air inlet pipeline can also directly introduce the precursor gas.

[0033] Before the deposition begins, the basic powder is first loaded into the reaction tank 1 of the deposition equipment, and the various precursors are placed in the corresponding raw material tanks. It should be noted that when there are multiple precursors, multiple raw material tanks need to be prepared. In some embodiments, the raw material tank may be introduced with a gaseous precursor. In more cases, a liquid or solid precursor is added to the raw material tank, which is heated to form a precursor gas and then participates in chemical vapor deposition.

[0034] Then, the first valve 5 and the second valve 6 are closed, and the reaction tank 1 is evacuated by the vacuum pump 4. This step is to reduce the generation of other substances when the precursor gas reacts in the reaction tank, and also helps to keep the basic powder in suspension for a long time.

[0035] During the preparation process, the raw material tank and the reaction tank need to be heated to make the various precursors phase-converted into precursor gases. In order to better mix the various precursor gases and make them fully react, the first valve 5 and the second valve 6 are opened, and an inert gas is introduced into the raw material tank, so that the inert gas carries the decomposed precursor gas in the raw material tank to the reaction tank. During the deposition process, the temperature of the reaction tank needs to be kept greater than or equal to the reaction temperature of all precursors.

[0036] In order to ensure that the basic powder can be suspended in the air and form better contact with the reactants, during the deposition process, the rotation speed of the reaction tank is set to 30-50rpm.

[0037] The present application further discloses a method for preparing a flexible green ceramic tape, comprising the steps of preparing a ceramic powder having a core-shell structure by the preparation method, and mixing and stirring the ceramic powder having a core-shell structure with an additive to form a slurry, and casting and drying the slurry to obtain a flexible green ceramic tape.

[0038] Since the ceramic powder is first made into a composite powder with a core-shell structure, it has good dispersibility. Therefore, in some embodiments, no dispersant may be added during the production of the green ceramic tape. However, the present application does not exclude the addition of a dispersant in some embodiments in order to obtain a green ceramic tape with more uniform and better ceramic powder dispersion.

[0039] Since the shell material in the ceramic powder of the core-shell structure acts as a binder in the subsequent ceramic sintering process, generally speaking, when the ceramic powder of the core-shell material prepared by this method is configured into a slurry, there is no need to add a binder component to the additive. Therefore, under normal circumstances, the additive includes a solvent and a plasticizer, and it is not ruled out that in some cases, the plasticizer itself is added in liquid form, which acts as both a plasticizer and a solvent. Since the ceramic powder of the core-shell material itself has very good dispersibility, the amount of dispersant added in the additive can also be reduced, or no dispersant is added, and the staff can adjust it as appropriate.

[0040] The solvent may be selected from: water, ethanol, isopropanol, xylene or a mixture of two or more thereof; the dispersant may be selected from: German BYK-22552, castor oil, TEGO-700 or the like or more; the plasticizer may be selected from: glycerol, ethylene glycol, dibutyl phthalate or the like or more.

[0041] The content of organic additives is related to the performance of the tape-casting slurry and is ultimately reflected in the quality of the green tape. Binders and plasticizers are the main organic additives in the tape-casting slurry. During the tape-casting molding and subsequent drying process, all powders and other additives are combined into a three-dimensional network structure, which determines the strength, toughness and lamination performance of the green tape. Plasticizers are used to soften the long chains of the binder, allowing them to stretch or deflect under stress to obtain better flexibility. When the binder content is too high, the green tape obtained has high strength but low toughness and is brittle, and is prone to defects in subsequent punching, lamination and other processes.

[0042] In the present application, by using ceramic powder of core-shell material, the proportion of binder in the slurry system is reduced, and the sintered ceramic will have higher strength, higher fracture toughness, and the advantage of high density. Specifically, the mass ratio of ceramic powder to additive is 8-12:1, for example 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, 12:1, etc. In the preferred implementation, the mass ratio of ceramic powder of core-shell structure to additive is 10:1. At this ratio, the raw porcelain tape has appropriate strength and toughness, which is convenient for subsequent punching, lamination and screen printing operations.

[0043] The above-mentioned method for preparing the raw porcelain tape has the following advantages: It solves the problems of uneven mixing and particle breakage caused by long-term mixing in ball milling; The binder wrapping effect is better, making the process of sintering ceramic materials (such as LTCC) after stacking green ceramic tapes more controllable, and the ceramic materials are not prone to agglomeration; The ratio of binder to slurry in the ceramic slurry prepared by this method will be further reduced, and the ceramic after sintering will have advantages such as higher strength, higher fracture toughness, and greater density.

[0044] The present application further discloses an application of ceramic powder prepared by rotary chemical vapor deposition in the preparation of green porcelain tape, wherein a high molecular polymer shell is formed on the surface of a basic powder by rotary chemical vapor deposition to form a ceramic powder with a core-shell structure, and the ceramic powder with a core-shell structure is used to prepare green porcelain tape. Example

[0045] S0. Prepare basic powder and precursor; S1. Load the basic powder into the reaction tank of the deposition equipment, put the precursors: benzene tetracarboxylic dianhydride (PMDA) and diaminohexane (DAH) into the corresponding raw material tank, and connect the raw material tank to the reaction tank of the deposition equipment; S2. Evacuate the reaction tank and keep the reaction tank in a vacuum state of less than 100 Pa during the deposition process; S3. Heating the reaction tank and ensuring that the temperature in the reaction tank is greater than or equal to the reaction temperature of each precursor during the deposition process, generally between 300-500°C; S4. The raw material tank is heated to change the precursor into a gas, and the temperature is controlled between 150-250°C. Steps S3 and S4 are performed in no particular order; S5. The reaction tank is kept at a rotation speed of 30-50 rpm, so that the basic powder can be suspended in the air in the reaction tank and dispersed evenly, and the precursor gas can be in uniform contact with the basic powder and effectively deposited on the surface of the basic powder; S6. The precursor gas decomposed in the raw material tank is carried into the reaction tank by Ar gas, and the ventilation flow rate is 20-160sccm; a variety of precursor gases can be set to different flow rates and different flow rates to enter the reaction tank according to specific needs, so as to achieve effective deposition on the surface of the basic powder; S7. After the reaction is completed, the ceramic powder having a core-shell structure is collected; S8. Mix the ceramic powder and the additives, and stir them thoroughly to obtain a ceramic slurry. In this system, the mass ratio of basic powder: solvent: dispersant: binder: plasticizer is 10: 0.6: 0.02: 0.15: 0.08, and the additives include: solvent, plasticizer and dispersant. The solvent is a mixture of water and ethanol, the dispersant is BYK-22552 from Germany, and the plasticizer is glycerol.

[0046] S9. The ceramic slurry is cast, dried and cut to obtain a flexible raw porcelain tape; S10. The flexible green ceramic tapes are stacked in multiple layers and then sintered to obtain low-temperature ceramic sheets.

[0047] The green porcelain tape obtained in Example 1 was placed under an electron microscope for observation. Figure 3 As shown, it can be seen that the surface of the green porcelain belt is dense, the ceramic particles are evenly distributed, and there are no obvious holes or cracks. Example

[0048] The difference between Example 2 and Example 1 is that the precursor material in S1 is replaced with a diacyl chloride and a diol complex to obtain a ceramic powder with a shell of polyvinyl butyral (PVB) material. The solvent in step S8 is a mixture of water and ethanol, the dispersant is castor oil, and the plasticizer is ethylene glycol. In this slurry system, the mass ratio of basic powder: solvent: dispersant: binder: plasticizer = 10: 0.6: 0.02: 0.15: 0.08. Example

[0049] The difference between Example 3 and Example 1 is that the precursor material in S1 is replaced with a diisocyanate and diol complex to obtain a ceramic powder with a shell of polyvinyl alcohol (PVA) material. The solvent is a mixture of ethanol, isopropanol, and xylene, the dispersant is castor oil, and the plasticizer is dibutyl phthalate. In the slurry system, by mass ratio, basic powder: solvent: dispersant: binder: plasticizer = 10: 0.6: 0.02: 0.15: 0.08.

[0050] Comparative Example The green tape is produced by ball milling and the ceramics are fired.

[0051] Solvent, dispersant, ceramic powder and alumina powder are added to a ball mill for a first ball milling. After the first ball milling, a binder and a plasticizer are added for a second ball milling. The binder is polyimide (PMMA), the solvent is a mixture of ethanol, isopropanol and xylene, the dispersant is castor oil, and the plasticizer is dibutyl phthalate. In the mixed ceramic slurry system, the mass ratio of ceramic to alumina powder: solvent: dispersant: binder: plasticizer is 10: 0.6: 0.02: 0.3: 0.08.

[0052] The green ceramic tape obtained by ball milling in the comparative example was observed under an electron microscope. Figure 2 As shown, it can be found that the surface of the green porcelain tape has obvious cracks and holes, which is caused by the uneven mixing during the ball milling process.

[0053] The slurries, green porcelain tapes and ceramic sheets fired with the green porcelain tapes obtained in the above-mentioned Examples 1-3 and Comparative Examples were respectively tested, and the following parameters were tested to obtain the data in Table 1.

[0054] Table 1 The density of raw porcelain is mainly determined by the solid content, that is, the mass proportion of the powder. The invention proposed in this paper can reduce the proportion of the organic phase in the overall slurry under the conditions of meeting the application. The raw porcelain production process requires a certain toughness to be made by tape casting. Generally speaking, the viscosity of the slurry does not exceed 4000mP.s, which is more suitable for tape casting. In the comparative example, the tape casting performance of the slurry is poor. In addition, due to the defect that the ball milling method cannot mix evenly, even if the content of the binder is artificially reduced, holes and cracks will appear in the raw porcelain sheet.

[0055] At the same time, in the three embodiments of the present application, the viscosity of the slurry after mixing is moderate, which is more suitable for tape casting, and the ceramic after sintering has a high density and strength. In the ball milling scheme, the proportion of the binder content cannot be controlled to be small enough. If it is too small, the slurry mixing is not uniform enough, and holes will appear in the raw porcelain. The content of the binder cannot be increased blindly, which will increase the viscosity of the slurry, making it impossible to carry out the tape casting process, and a large number of holes will appear in the sintered ceramics, affecting the mechanical strength.

[0056] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and the scope of protection of the present invention is defined by the attached claims, description and their equivalents.

Claims

1. A method for preparing a ceramic powder having a core-shell structure, characterized in that: The invention adopts a rotary chemical vapor deposition method to mix a basic powder with a plurality of precursor materials for forming a shell material, and react the plurality of precursor materials at a reaction temperature to generate a high molecular polymer shell outside the basic powder.

2. The preparation method according to claim 1, characterized in that: The basic powder is a mixture of one or more materials selected from ceramics, glass and alumina.

3. The preparation method according to claim 1, characterized in that: The high molecular polymer shell is polyimide, polyvinyl butyral or polyvinylidene fluoride.

4. The preparation method according to claim 3, characterized in that: The high molecular polymer shell is polyimide, and the precursor material includes benzenetetracarboxylic dianhydride and diaminohexane.

5. The preparation method according to claim 1, characterized in that: Before the deposition begins, the basic powder is loaded into a reaction tank of a deposition device, and the reaction tank is evacuated; and the plurality of precursors are added into corresponding raw material tanks.

6. The preparation method according to claim 5, characterized in that: The raw material tank is heated to make the multiple precursors undergo phase change to form gas, the raw material tank is connected to a reaction tank of a deposition device, and the temperature of the reaction tank is maintained to be greater than or equal to the reaction temperature of each of the precursors.

7. The preparation method according to claim 6, characterized in that: Inert gas is introduced into the raw material tank, so that the inert gas carries the decomposed precursor gas in the raw material tank to the reaction tank.

8. The preparation method according to claim 7, characterized in that: The flow rate of the inert gas is 20-160 sccm.

9. The preparation method according to claim 5, characterized in that: During the deposition process, the rotation speed of the reaction tank is set to 30-50 rpm.

10. The preparation method according to claim 1, characterized in that: The steps include: S1. Loading the basic powder into the reaction tank of the deposition equipment, and placing the plurality of precursor materials into the corresponding raw material tanks respectively; S2. Evacuate the reaction tank to make the pressure inside the reaction tank less than 100Pa; S3. The reaction tank and the raw material tank are heated, the reaction tank temperature is maintained at 300-500°C, and the raw material tank temperature is maintained at 150-250°C, so that the precursor phase changes to form a gas; S4. Connecting the raw material tank and the reaction tank, introducing an inert gas into the raw material tank, carrying the precursor gas to the deposition tank, wherein the ventilation flow rate of the inert gas is 20-160sccm; S5. During the deposition process, the reaction tank is kept at a rotation speed of 30-50 rpm, so that the basic powder is evenly suspended in the mid-air in the reaction tank, so that the precursor can be evenly contacted with the basic powder, and react and deposit on the surface of the powder; S6. After the reaction is completed, the ceramic powder with the polymer shell is collected.

11. A method for preparing a green porcelain tape, characterized in that: The method comprises the steps of preparing a ceramic powder having a core-shell structure by the preparation method as described in any one of claims 1 to 10, and mixing and stirring the ceramic powder having a core-shell structure with an additive to form a slurry, and using the slurry to prepare a flexible green ceramic tape.

12. The preparation method according to claim 11, characterized in that: The additive does not contain a dispersant.

13. The preparation method according to claim 11, characterized in that: The mass ratio of the ceramic powder to the additive is 8-12:

1.

14. The preparation method according to claim 11, characterized in that: The additives include a plasticizer; or, the additives include a solvent and a plasticizer; or, the additives include a binder, a solvent and a plasticizer; or, the additives include a solvent, a binder, a plasticizer and a dispersant.

15. An application of ceramic powder prepared by rotary chemical vapor deposition in the preparation of green porcelain tape, wherein a high molecular polymer shell is formed on the surface of a basic powder by rotary chemical vapor deposition to form a ceramic powder with a core-shell structure, and the ceramic powder with a core-shell structure is used to prepare green porcelain tape.

Citation Information

Patent Citations

  • Preparation method for high solid content aqueous tape-casting slurry of cerium oxide-based ceramic particles

    CN102219516A

  • Powder rotating CVD (chemical vapor deposition) device

    CN103668112A

  • Preparation method of aluminum oxide-carbon nano tube composite powder material

    CN105198447A

  • Process and device for preparing nano-scale core-shell structured carbon-coated composite material

    CN109873135A

  • Preparation method of alumina-zirconia nano composite powder

    CN113620329A

Cited By

  • Method for preparing high-frequency low-loss LTCC (Low Temperature Co-Fired Ceramic) material by utilizing external doping means

    CN121005573A